Effect of Collection Seasons on the Oocyte Quality and Developmental Competence of Oocytes Derived from Korean Native Cows (Hanwoo) by Ovum Pick-Up - Seong-Su Kim; Byung Hyun Choi; Hyun-Tae Jo; Jong-In Jin; A-Na Ha; Chan-Sik Min; Gyu-Wan Cho; Il-Keun Kong (The Korean Society of Animal Reproduction and Biotechnology, 2014)
Implementation of smart embryo technologies in cattle e.g. ovum pick-up followed by in vitro embryo production (OPU-IVP). Seasonal variation is important factor for follicular growth, oocytes quality, quantity and developmental competence. Therefore the aim of present study was carried out to investigated whether the seasons (hot and cool) effect on follicular development, oocyte recovery and subsequent embryo development. Follicular oocytes were aspirated from Korean native cows (Hanwoo) by the ovum pick-up (OPU) method, which was performed 24 times during two different seasons, the hot (July to September) and cool (October to December), from OPU donors. The recovered oocytes were classified according to morphological categories and used for in vitro embryo production (IVEP). The mean number of total follicles was significantly higher (p<0.05) during the hot season (18.32 ± 2.26) compared to cool season (15.41 ± 3.34). Furthermore, seasons did not significantly effect on the number of oocytes recovered (hot season: 41.16% vs. cool season: 46.14%). However, the average number of Grade A oocytes was significantly greater during hot (1.75 ± 1.86) season compared to the cool season (1.00 ± 1.46), but there was no significant difference of other grades oocytes. The cleavage rate (hot: 66.67% vs. cool: 63.3%) and embryo development (hot: 58.95% vs. cool: 56.97%) did not differ significantly between the seasons. In conclusion, the results of present study suggest that the season (hot and cool) does not have effects on the oocyte recovery and embryo developmental competence of in vitro cultured embryos.